Targeting human Acyl-CoA:cholesterol acyltransferase as a dual viral and T cell metabolic checkpoint - Nathalie M. Schmidt (Nature Portfolio, 2021)
Shared metabolic pathways could allow simultaneous manipulation of T cells, viruses and tumours. Here the authors show targeting cholesterol esterification restrains hepatitis B in vitro, whilst bolstering exhausted antigen-specific T cell responses from human liver and hepatocellular carcinoma.